The Effect Of Perceived Ease And Risk On The Interest In Using Financial Technology (Fintech) Dana Among The Community In Bengkulu City - Alita Riri; Neri Susanti; Lydia Gustina Putri (Utami Publisher, 2026)
This research is motivated by the increasing use of digital financial services, including financial technology (Fintech) applications such as DANA, in Bengkulu City, which are considered practical and efficient. However, there are still differences in public perception regarding the ease and risks of using the DANA application. This study aims to determine the influence of perceived ease and risk on public interest in using DANA financial technology (Fintech) among residents of Bengkulu City. A quantitative associative approach was used. A sample of 100 respondents was selected using a purposive sampling technique, with the criteria being DANA application users and residing in Bengkulu City. Data were collected through questionnaires and analyzed using validity and reliability tests, multiple linear regression, t-tests, F-tests, and coefficients of determination (R2) using SPSS. The results showed that each instrument was valid and reliable. The multiple linear regression test produces the equation Y = 0.364 + 0.081X1 + 0.904X2 + e and the results of the t test at a significance level of 0.05 explain that partially X1 has no significant effect on Y with a tsig value > α (0.444 > 0.05), X2 has a significant effect on Y with a tsig value < α (0.000 < 0.05). The F test obtained F count 137.645 > F table 3.09 with a significance of 0.000 < 0.05, thus, it can be concluded that together the independent variables influence the dependent variable. The coefficient of determination (R2) value of 0.734 indicates that 73.4% of the variation in interest in using is explained by perceived ease and risk, while 26.6% is influenced by other variables outside the study. These findings, in which risk is dominant and perceived ease of use is insignificant, are expected to serve as a guide for Fintech developers to improve security, ease of use, and public interest.